A protocol for a discrete choice experiment: understanding patient medicine preferences for managing chronic non-cancer pain - Marian Shanahan; Suzanne Nielsen; Briony Larance; Milton Cohen; Maria Schaffer; Gabrielle Campbell (BMJ Open)
Introduction High rates of chronic non-cancer pain (CNCP), concerns about adverse effects including dependence among those prescribed potent pain medicines, the recent evidence supporting active rather than passive management strategies and a lack of funding for holistic programme have resulted in challenges around decision making for treatment among clinicians and their patients. Discrete choice experiments (DCEs) are one way of assessing and valuing treatment preferences. Here, we outline a protocol for a study that assesses patient preferences for CNCP treatment.Methods and analysis A final list of attributes (and their levels) for the DCE was generated using a detailed iterative process. This included a literature review, a focus group and individual interviews with those with CNCP and clinicians who treat people with CNCP. From this process a list of attributes was obtained. Following a review by study investigators including pain and addiction specialists, pharmacists and epidemiologists, the final list of attributes was selected (number of medications, risk of addiction, side effects, pain interference, activity goals, source of information on pain, provider of pain care and out-of-pocket costs). Specialised software was used to construct an experimental design for the survey. The survey will be administered to two groups of participants, those from a longitudinal cohort of patients receiving opioids for CNCP and a convenience sample of patients recruited through Australia’s leading pain advocacy body (Painaustralia) and their social media and website. The data from the two participant groups will be initially analysed separately, as their demographic and clinical characteristics may differ substantially (in terms of age, duration of pain and current treatment modality). Mixed logit and latent class analysis will be used to explore heterogeneity of responses.Ethics and dissemination Ethics approval was obtained from the University of New South Wales Sydney Human Ethics committee HC16511 (for the focus group discussions, the one-on-one interviews and online survey) and HC16916 (for the cohort). A lay summary will be made available on the National Drug and Alcohol Research Centre website and Painaustralia’s website. Peer review papers will be submitted, and it is expected the results will be presented at relevant pain management conferences nationally and internationally. These results will also be used to improve understanding of treatment goals between clinicians and those with CNCP.